The mediating role of students' academic resilience in the relationship between self-efficacy and test anxiety - Ali Asghar Hayat; Hydar Choupani; Hatam Faraji Dehsorkhi (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: There is growing acknowledgment that medical education can be a stressful experience for students and may have a devastating effect on their psychological well-being. The present article, therefore, aimed at investigating students' academic resilience as a mediating variable in self-efficacy-test anxiety relation. MATERIALS AND METHODS: In this cross-sectional correlational study, a convenience sample of 243 medical students was selected and participated, three prevalidated questionnaires were applied, that is, general self-efficacy questionnaire, academic resilience questionnaire, and test anxiety questionnaire. To analyze the data, Pearson's correlation coefficient as well as structural equation modeling (SEM) were used. RESULTS: According to Pearson's coefficients, self-efficacy was found to be positively correlated with academic resilience (r = 0.437, P ≤ 0.01) and negatively with test anxiety (r = −0.475, P ≤ 0.01). SEM results also indicated that self-efficacy positively impacts on academic resilience (β = 0.43, P < 0.001) and negatively on test anxiety (β = −0.37, P < 0.001). In addition, results demonstrated the mediating role of academic resilience in self-efficacy-test anxiety relationship (β = −0.108, P < 0.001). CONCLUSION: This study showed that academic resilience could play a mediating role in students' self-efficacy-test anxiety relationship.